Assessing the Moderating Effect of Bank Size on the Interaction between Bank Health Level and Company Value in Digital Banks - Ilmi, Mainatul; Muhdar, Muhdar; Handayani, Yuniorita Indah (Magister Akuntansi Universitas Pancasila, 2024)
Purpose: This study aims to analyze the effect of bank health level using the RGEC method on company value with bank size as a moderating variable in digital banks registered with the OJK Republic Indonesia in 2021-2023. Methodology: The population of this study was 15 companies. The sampling technique used purposive sampling for 7 companies. The data analysis method used Moderating Structural Equation Modelling (MSEM) with Smart-PLS 4. Finding: The results of the study show that bank health level and bank size affects the company value. Bank size can strengthen the influence of bank health level on the company value. Implication: This study provides insight to digital banks in Indonesia where it is necessary to pay attention to bank health level factors that can affect company value as a reflection of investor assessments in making investment decisions. Such as risk profile, GCG, and earnings factors which play a very important role in describing the health condition of a bank. The other side, companies must be able to optimize the use of bank capital for productive activities that can generate profits. Bank size is also considered by investors so it affects the company value. Originality: the originality of this study is in the innovative methodological approach and relevant practical implications. This study uses bank size as a moderating variable. Analysis with a moderation effect is used to test whether the moderating variable can strengthen or weaken the influence between the exogenous variables and the endogenous variable.